PERAN BAWASLU KOTA DEPOK DALAM MENGAWASI PELANGGARAN NETRALITAS ASN PADA PILKADA KOTA DEPOK 2020 - Joseph Taruli Stephanus (2022)
This paper examines the efforts made by the Depok City Bawaslu in overseeing violations of the Neutrality of the State Civil Apparatus in the 2020 Depok City Regional Head General Election during the COVID-19 pandemic. .The risk of the State Civil Apparatus being not neutral during the general election for regional heads is of course a big task for Bawaslu in supervising the State Civil Apparatus. .The efforts made by Bawaslu are reviewed in this paper so that readers can find out how the role of Bawaslu is in overseeing violations of the neutrality of the State Civil Apparatus, as well as explaining what has contributed to the success and obstacles of Bawaslu's role in handling casesviolation of the Neutrality of the State Civil Apparatus.